Development of a Waste Management Application Using AppSheet: A Case Study of North Bangkok University - มาตรหมาย พิชชาภา; อินต๊ะนา รุ่งทิพย์; ปานสุวรรณ ดุสิตา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1) develop a waste management application using AppSheet for a case study at North Bangkok University, 2) evaluate the application’s quality by information technology experts, and 3) assess user satisfaction. The participants were 30 students from North Bangkok University, selected through purposive sampling. The research instruments included the AppSheet-based application, an expert evaluation form, and a user satisfaction questionnaire. Data were analyzed using mean and standard deviation. The results indicated that the application efficiently managed waste data, featuring functions for waste type scanning, data recording, and a point-based reward system to encourage participation. Expert evaluation showed a high-quality rating (x̄= 3.99, S.D. = 0.17), and user satisfaction was also high (x̄= 4.38, S.D. = 0.04). In conclusion, the application is of appropriate quality, capable of supporting waste management, and effectively promotes proper waste segregation behavior within the university.